Avaliação da qualidade de vida de pacientes acometidos por Diabetes Mellitus Tipo 1 tratados com análogo de insulina Glargina versus insulina NPH - Paulo Henrique Ribeiro Fernandes Almeida (2017)
INTRODUCTION: Diabetes Mellitus (DM) is a chronic disease that requires continuous medical care. In this sense, which is the way of life with a commitment to quality of life (QoL) over time. It is responsible for millions of people around the world per year, and can be subdivided into Type 1 Diabetes Mellitus (DM1), Type 2 Diabetes Mellitus (DM2) and other forms of DM. The treatment of DM1 consists of the replacement of non-produced insulin endogenously, a so-called insulin therapy. Insulin glargine analogue (GLA) has been used without treatment of patients with DM1 and in theory would be associated with better QoL of patients compared to treatment with a human insulin Neutral Protamine Hagedorn (NPH), however assumption still lacks a confirmation with better evidence. OBJECTIVE: To evaluate the QOL of patients with DM1 who use GLA in comparison to NPH. METHODS: A) Systematic review - A systematic review (RS), which included randomized controlled trials (RCTs) and cohorts (concurrent and non-concurrent), was available from PUBMED (Medline), EMBASE, LILACS, Cochrane Library ( accessed through January 2017), as well as manual search in magazines and gray literature. The primary outcome was QOL and glycated hemoglobin (HbA1c) as secondary. Methodological quality was assessed by Cochrane risk of bias and Newcastle-Ottawa scale. Due to the heterogeneity of the instruments used to evaluate QoL in the studies, the results were presented in a quantitative way. B) Cross-sectional study - an analytical-descriptive study conducted in Minas Gerais with 401 patients with DM1 using GLA and 179 patients using NPH. A three-part questionnaire was applied: sociodemographic aspects; clinical aspects related to access to health services; and the generic instrument, Euroqol, of QV (EQ-5D-3L). A normality test was performed for the EQ-5D-3L utilities. The dichotomous and descriptive variables were reported by relative and absolute frequencies, continuous variables were reported on average, standard deviation (SD) and confidence interval (95% CI). A multiple regression was performed with sociodemographic predictors, clinical data and access to health services with the EQ-5D-3L utilities as response variables, adopting a significance level of 0.05. RESULTS: A) Systematic review - There were 634 publications in the electronic databases, including eleven publications (four cohorts and four RCTs). Of the six instruments used to measure QOL, the most used was the DTSQs (Diabetes Treatment Satisfaction Questionnaire). Cohort studies obtained moderate methodological quality and ERCs were considered to be of poor quality. The domain of the DTSQs instrument designated for treatment satisfaction obtained a better score favoring GLA. However, the other instruments did not show an improvement in the QoL of patients using GLA. Regarding HbA1c, no desirable values were observed in glycemic control in GLA treated patients when compared to NPH. B) Cross-sectional study Of the 580 patients evaluated, 54% (n = 313) were women, with an age range of 21-40 years old (n = 212) with a mean age of 43.86 years (95% CI = 42.31-45.41) . Patients with DM1 who used GLA had better sociodemographic conditions compared to NPH, were younger, had more schooling and had social stratification B1 or higher. As for the clinical outcomes, individuals who used GLA had a better perception of their health with fewer bouts of severe and non-severe hypoglycemia compared to NPH, as well as greater access to health insurance compared. The QQ scores of the EQ-5D-3L instrument were higher and presented statistical significance for the GLA group compared to NPH. As for the factors associated with a better QoL, measured by multiple regression, being young, self-perception of good / good health, not having been bedridden, none to three medical appointments, no hospitalization, physical exercise, between zero and three comorbidities having severe hypoglycemia, were responsible for explaining a better QoL (41.3%). CONCLUSIONS: A) Systematic Review - The findings obtained by this SR did not show improvement in the QOL score with the use of GLA in detriment of NPH. Only in the treatment satisfaction domain, measured by the DTSQs instrument, favorable results were observed for GLA. B) Cross-sectional study - In the opinion of the GLA users to obtain a better QoL score in the EQ-5D-3L, the insulin therapy was not linked to a better QoL of patients with DM1. A better QoL is associated with a better sociodemographic and clinical condition. Moreover, the socioeconomic differences between the GLA and NPH groups point to a possible inequality in GLA access.